Biochemical and histological evaluation of Garcinia mangostana linn. on streptozotocin-induced diabetic rats - Tg Zakaria, Tg Muhammad Faris Syafiq; Bakhtiar, M. Taher; Azad, Abul Kalam (2013)
The aim of the present study was to evaluate the biochemical effects and histopathological alterations of the ethanolic extracts of Garcinia mangostana pericarps (GME) on STZ-induced diabetic rats. Oral administration of GME at doses of 50, 100 and 200 mg/kg b.w. were given to STZ-induced diabetic and normoglycaemic albino rats. The serum biochemical parameters, enzymatic analysis and histopathological alterations were examined and compared to reference standard hypoglycamic drug, glibenclamide. Analytes including blood glucose, liver transminases viz. alanine aminotransferase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALT), lipid profile included triglycerides (TG), total cholesterol (TC), high density lipoprotein (HDL), Low density lipoprotein (LDL) and very low density lipoprotein (VLDL); creatinine, urea and total protein were checked using standard test kits and reagents. Histological changes in the liver, kidney and pancreas of the animals were also examined. The results obtained revealed a significant reduction of glucose level in GME with doses of 100 mg/kg (p<0.00l) and 200 mg/kg (p<0.00l) compared to 50 mg/kg. Total cholesterol, serum triglyceride, LDL, VLDL, urea and creatinine were reduced in the treatment group while total protein contents and HDL level mildly elevated. Histological assessment revealed a reduction in lesions associated with diabetic state in STZ-induced rats. The implications of the results obtained especially the reduction in glucose and improved biochemical function by G. mangostana suggested their potential to use GME in the management of diabetes when administered in dose-dependent manner.